Pengembangan Bahan Ajar Praktikum Berbasis Teaching Factory di Politeknik Industri Logam Morowali - Hendi Lilih Wijayanto (SAP (Susunan Artikel Pendidikan), 2023)
This development is based on observations and evaluations during eight months of teaching at the Morowali Metal Industry Polytechnic, especially in the production and machining Engineering II course. The result was, due to a lack of learning resources for production and machining practicum II which were linked to polytechnic vocational based on teaching factory learning, which has not been maximally implemented at the Morowali Metal Industry Polytechnic. The purpose of developing this teaching material was to produce a teaching factory-based production and machining practicum learning device II where the output was product learning in 2022 using the observation and interview method, which have not implemented learning products that were useful and had economic value as ready-to-use teaching factory products marketed. Through distance learning, the author was raising issues according to the experience above, the main issue was that the practicum module which has not yet linked and matched with the teaching factory. The output of the author's research activities was in the form of practicum modules and other learning tools which the learning products were lathes, which at least met the practical needs of the Mechanical Maintenance Engineering Study Program.